Brief report: The role of three dimensions of sexual well-being in adolescents' life satisfaction. (February 2017) - Espinosa-Hernández, Graciela; Vasilenko, Sara A.; McPherson, Jenna L.; Gutierrez, Estefania; Rodriguez, Andrea
Abstract: Guided by theoretical (Brooks-Gunn & Paikoff, 1997) and empirical work (Horne & Zimmer-Gembeck, 2005), this cross-sectional study examined whether sexual well-being (sexual self-acceptance, importance of mutual consent, importance of safe sex) was associated with life satisfaction among Mexican adolescents, and whether these associations were moderated by gender, age, and familism. Mexican adolescents (54% girls, 72% middle schoolers, 30% sexually active) completed surveys. Findings indicated that a greater belief in the importance of safe sex was associated with higher levels of life satisfaction. Greater sexual self-acceptance was associated with life satisfaction, and familism moderated this association. This association was stronger among adolescents who reported low familism. This study contributes to the understanding of sexual adolescent well-being and psychological adjustment in Mexico, an understudied cultural context.